Pencampuran Warna dalam Finger Painting pada Kelompok B di RA Al Anwar Kota Kediri - Zulfa, Lutfiyati Unsiyah; Hibana, Hibana (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to examine how the process of preparing color mixing activities, the process of implementing color mixing activities, and the benefits of color mixing activities in group B at PAUD RA Al Anwar Kediri City. The research method used is descriptive qualitative research, a sample of 15 children taken by observation technique. The data collection process is by conducting interviews, participant observation, and documentation. Data analysis in this study uses narrative analysis techniques and is obtained by using data collection, data reduction, data display, verification and confirmation of conclusions. The results showed that Finger Painting activities are very beneficial for students, inseparable for further education such as stimulation for daily activities, coordination between brain and eyes, brain development, and imagination. The conclusion in this study is that Finger Painting color play activities can maximize the various skills possessed by children. Because color play can encourage children's willingness to move freely and create images. Keywords: Finger Painting, Color mixing, Group B.